Influence of cryopreservation on structure and function of mammalian spermatozoa: an overview - Ezzati, Maryam; Shanehbandi, Dariush; Hamdi, Kobra; Rahbar, Sara; Pashaiasl, Maryam (Cell and tissue banking, 2020)
Cryopreservation is a useful approach to preserve male fertility for assisted reproduction technique and other evaluations. In spite of extensive development in the cryopreservation field, there are biological and biochemical points including DNA fragmentation and antioxidant which should be illuminated to preserve fertility in safe form. Several molecular markers such as coding and noncoding RNAs are transferred from spermatozoa into oocyte via fertilization. These biomarkers affect fertility potential during the cryopreservation. Despite its impact, sperm cryopreservation has some destructive effect including loss of sperm motility and viability, acrosomal damage, mitochondrial membrane depolarization, plasma membrane permeability alteration even nuclear, and DNA damage. There is a growing concern about the impact of sperm cryopreservation on biological factors which can interrupt successful fertility procedures such as in vitro fertilization. Additionally, cryo-damage can decrease embryonic development extent. Promoting cryopreservation method via investigating the wide range of non-invasive factors may be increasingly important to have access to safe approach of freezing. Therefore, the aim of this study is the assessment of biological factors which can penetrate the fertility potential during the freezing procedure, explicate innovative methods in fertility preservation.